Kemampuan Berpikir Kritis Matematis Siswa SMA ditinjau dari Self Efficacy: Studi pada Materi Fungsi Aljabar - Akbar Nor Alam; Ade Hilda Zainy Aditya; Tika Karlina Rachmawati; Hamdan Sugilar (Gunung Djati Conference Series, 2026)
The purpose of this study is to evaluate the mathematical critical thinking ability of eleventh-grade students from an independence perspective; comparative and inverse value materials are used to assess this ability. This exploratory study uses a qualitative descriptive approach. This study involved 30 eleventh-grade students at a high school in Bandung City. With a focus on three subjects: high, medium, and low self-efficacy. The instruments used in this study are questionnaires on Mathematical Critical Thinking Ability (KBKM), interviews, and self-efficacy questionnaires. Check the data with time triangulation. The results of the study show that: (1) students with a high level of self-efficacy have excellent KBKM; (2) students with a medium level of self-efficacy have moderate KBKM; and (3) students with a low level of self-efficacy have poor KBKM. As a result, teachers must pay attention to the components of the student independence scale when training students' critical thinking skills in mathematics